How Principals of Madrasah Ibtidaiyah Negeri Dealt with Obstacles - Amalia Hasanah; Ummi Kultsum (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2020)
This study was intended to find out how principals of Madrasah Ibtidaiyah Negeri (MIN) in remote regions in South Sumatra dealt with obstacles of shortage of permanent teachers and lack of infrastructure. This study was a qualitative interpretivist study. Semi-structure interviews and observations were implemented to collect the data. Four MIN principals in remote regions in two districts in South Sumatra were interviewed. The results showed that to overcome the shortage of permanent teachers, the principals took the non-permanent teachers to be in charge as homeroom teachers and placed teachers available to teach subjects that were not suitable with their education background. To overcome the lack of infrastructure, the principals used available rooms in the school for other purposes needed, used the classes in turn, and limited the number of students enrolled in the school.